Secularization of immigration policy vs. religion's influence on integration: Israel's non‐Jewish Jews' immigration in a comparative perspective. Issue 1 (28th September 2018) - Fisher, Netanel
Abstract: This article deals with the complex relationship between religion and immigration in Western countries, with an emphasis on Israel. The main argument it presents is that the legal procedures of immigration, i.e. laws relating to the acquisition of civil status, have undergone dramatic secularization, while religion's influence is expressed in the social and cultural aspects of the integration of immigrants belonging to religious minorities. This division reinforces the classical theory of secularization, as the formal boundaries of nations are not subject to religious affiliations, but it also supports the theories of competition and complementation between religion and secularism in the social sphere. The tension in the Israeli case between the immigration, naturalization and integration of non‐Jewish Jews, who are part of the extended Jewish population that is not defined by religious parameters, confirms this thesis. The immigration of hundreds of thousands of non‐Jewish Jews' under the Law of Return based on ethno‐national‐secular parameters is an ultimate expression of the secularization of Jewish nationality. On the other hand, the state's encouragement of non‐Jewish immigrants to convert to Judaism so that they can better assimilate into Jewish society signifies the importance of religion in the social integration aspect.